Chemotherapy and Target Therapy in the Management of Adult High- Grade Gliomas - Paolo Spinelli, Gian; Miele, Evelina; Lo Russo, Giuseppe; Miscusi, Massimo; Codacci-Pisanelli, Giovanni; Petrozza, Vincenzo; Papa, Anselmo; Frati, Luigi; Della Rocca, Carlo; Gulino, Alberto; Tomao, Silverio (Current Cancer Drug Targets, 2012)
Adult high grade gliomas (HGG) are the most frequent and fatal primary central nervous system (CNS) tumors. Despite recent advances in the knowledge of the pathology and the molecular features of this neoplasm, its prognosis remains poor. In the last years temozolomide (TMZ) has dramatically changed the life expectancy of these patients: the association of this drug with radiotherapy (RT), followed by TMZ alone, is the current standard of care. However, malignant gliomas often remain resistant to chemotherapy (CHT). Therefore, preclinical and clinical research efforts have been directed on identifying and understanding the different mechanisms of chemo-resistance operating in this subset of tumors,in order to develop effective strategies to overcome resistance. Moreover, the evidence of alterations in signal transduction pathways underlying tumor progression, has increased the number of trials investigating molecular target agents, such as anti-epidermal growth factor receptor (EGFR) and anti- vascular endothelial growth factor (VEGF) signaling. The purpose of this review is to point out the current standard of treatment and to explore new available target therapies in HGG.
Keywords: target therapy